Salvage nasoduodenal feeding for severely burned patients after the failure of nasogastric feeding: A medical center experience in a mass casualty burn disaster. Issue 4 (9th November 2018) - Kung, Chi‐Hao; Tseng, Yu‐Chen; Dai, Niann‐Tzyy; Chang, Wei‐Kuo; Hsieh, Tsai‐Yuan; Lin, Jung‐Chun
Abstract : Patients with major burn injuries have increased energy requirements. Aggressive nutrition support is recommended following severe burn injury, and early feeding is an established part of the management of these patients. However, the optimal method of feeding is still being debated because nasogastric feeding is often unsuccessful. The question of whether nasoduodenal tube feeding can provide a salvage means of providing enteral nutrition has not yet been examined. The aim of this study was to assess the general outcomes and safety of nasoduodenal tube feeding for patients with severe burn injuries after unsuccessful nasogastric feeding. In June 2015, after a mass casualty incident involving multiple burn victims, we reported our experience of enteral feeding of patients with major burn injuries. Eight patients who had failed on nasogastric feeding, due to gastric stasis, were started on nasoduodenal feeding. Outcome variables included daily caloric intake and changes in serum albumin levels. The mean caloric intake increased from 1373 ± 628 kcal/d before the insertion of a prenasoduodenal tube to 2345 ± 415 kcal/d on day 7 postinsertion ( P = 0.002). After converting to nasoduodenal feeding, no significant decrease in serum albumin levels ( P = 0.235) was reported. There were no deaths. Nasoduodenal tube feeding should be considered for all patients with major burn injuries who cannot tolerate nasogastric tube feeding.